2012
DOI: 10.1182/blood-2011-04-346098
|View full text |Cite
|
Sign up to set email alerts
|

Calcium- and integrin-binding protein 1 regulates megakaryocyte ploidy, adhesion, and migration

Abstract: Megakaryocytes are large, polyploid cells that produce platelets. We have previously reported that calcium-and integrin-binding protein 1 (CIB1) regulates endomitosis in Dami cells. To further characterize the role of CIB1 in megakaryopoiesis, we used a Cib1 ؊/؊ mouse model. Cib1 ؊/؊ mice have more platelets and BM megakaryocytes than wild-type (WT) controls (P < .05). Furthermore, subsequent analysis of megakaryocyte-CFU production revealed an increase with Cib1 deletion compared with WT (P < .05). In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…injection of 50 mg/kg anti-mouse CD41 antibody, and monitored recovery. After twenty-four hours we observed greater than 85% platelet reduction in both PKCy À/À and WT littermate control mice, which is consistent with previous reports [16,17]. However, recovery up to 7 days was unaltered with PKCy deficiency suggesting that PKCy does not contribute to in vivo megakaryopoiesis or platelet production ( Figure 2).…”
supporting
confidence: 81%
“…injection of 50 mg/kg anti-mouse CD41 antibody, and monitored recovery. After twenty-four hours we observed greater than 85% platelet reduction in both PKCy À/À and WT littermate control mice, which is consistent with previous reports [16,17]. However, recovery up to 7 days was unaltered with PKCy deficiency suggesting that PKCy does not contribute to in vivo megakaryopoiesis or platelet production ( Figure 2).…”
supporting
confidence: 81%
“…4 Previous studies were primarily focused on the early and middle stages of thrombopoiesis, including the commitment to MK lineage and the MK proliferation. 20,32 Here, we demonstrate that the sympathetic transmitters NE and EPI stimulate platelet production by promoting MK adhesion, migration, PPF and platelet release, in addition to the expansion of CD34 1 cells. These findings are consistent with our recent study that showed that human growth hormone treatment resulted in a quick increase in platelet production by regulating the late stage of thrombopoiesis, including the promotion of PPF and platelet release.…”
Section: Discussionmentioning
confidence: 99%
“…20,32,36 Furthermore, ERK1/2 activation downregulates the RhoA activity in mature MKs upon treatment with NE or EPI. These effects led to the rearrangement of the actin and microtublin cytoskeletons, which was a known key determinant for PPF, platelet formation, and platelet release.…”
Section: Discussionmentioning
confidence: 99%
“…35 DNA content in CD41 1 megakaryocytes was determined by labeling red blood celllysed bone marrow with anti-CD41-efluor450, followed by fixation with 0.5% formalin. Cells were permeabilized with 70% ice-cold methanol and washed and incubated with 10 mg RNase A, followed by brief incubation with 1 mg/mL propidium iodide.…”
Section: Megakaryocyte Ploidy Analysismentioning
confidence: 99%